2023
DOI: 10.3390/en16186542
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Study on Techno-Economic Evaluation of Hydrogen Production

Victor Hugo Souza de Abreu,
Victória Gonçalves Ferreira Pereira,
Laís Ferreira Crispino Proença
et al.

Abstract: This paper aims to perform a systematic review, with a bibliometric approach, of the techno-economic evaluation studies of hydrogen production. To achieve this objective, a comprehensive outline of hydrogen production processes from fossil and renewable sources is presented. The results reveal that electrolysis, classified as water splitting, is the most investigated process in the literature since it contributes to a reduction in greenhouse gas emissions and presents other advantages, such as maturity and app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…In a hybrid energy storage system, the storage state of the battery is determined by the previous moment's storage state and the actions taken at the current moment. This paper takes into account the energy dissipation in the battery and expresses its storage state according to (4).…”
Section: Hybrid Energy Storage Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In a hybrid energy storage system, the storage state of the battery is determined by the previous moment's storage state and the actions taken at the current moment. This paper takes into account the energy dissipation in the battery and expresses its storage state according to (4).…”
Section: Hybrid Energy Storage Systemmentioning
confidence: 99%
“…On the other hand, energy-type storage methods, like hydrogen storage, have longer storage durations but cannot accommodate rapid power fluctuations. Hydrogen storage, as a form of energy-based storage, has gained increasing attention due to the rise of the hydrogen industry and hydrogen-powered vehicles as a means to balance the volatility of renewable energy [4].…”
Section: Introductionmentioning
confidence: 99%
“…It often uses software modeling to estimate the cost of capital, operating cost, and revenue based on technical and financial input parameters [42]. In the literature, there are many different areas in which techno-economic analysis was conducted, such as typical dryers with different energy sources [43], various hydrogen production methods [44], biodiesel production [45] asteroid mining [46], hybrid energy systems [47], innovative steel production technologies [48], thermal energy storage [49], green ammonia production processes [50], alternative fuels [51], phytoremediation [52], water desalination [53,54], an isolated hybrid energy system [55], hybrid biomass renewable energy systems [56], hydrogen production [57], renewable fuel alternatives in the maritime sector [58], production [59], electric vehicle charging stations [60], and hydrogen refueling stations [61]. However, no study has been found on the techno-economic analysis of the physical material properties of wooden structures built by the sea under the influence of moisture and salt according to seasonal changes.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, hydrogen demand is expected to increase up to 158 Mt by 2030 [1], while the most economical and favored method for producing hydrogen on a commercial scale is through methane steam reforming [2]. Various intensification processes have been studied to increase the economic efficiency of hydrogen production through steam reforming.…”
Section: Introductionmentioning
confidence: 99%